Merger and timeliness of audit report / Hilwani Hariri ... [et al.] - Hariri, Hilwani; Abdul Rahman, Norshimah; Fauzee, Fairuz; Che Ahmad, Ayoib (Universiti Teknologi MARA, Perlis, 2006)
The audit profession underwent significant changes when two of its leading firms merged in 1998. The then Big 6 became Big 5 with the merger of PriceWaterhouse and Coopers and Lybrand to form PricewaterhouseCoopers. Some observers predicted that this merger would have implications of competition and concentration on the audit market. The purpose of this paper is to determine if the merger of the audit firms has any impact on audit delay or audit report lag (a crucial component of audit efficiency). Audit delay is measured as the difference between audit report date and balance sheet date. The annual reports of client companies of both firms before the merger (1996, 1997 and 1998) and post merger (1999, 2000 and 2001) were examined. The panel data regression technique was utilized to examine the pooled data. The results show that the merger reduced the audit delay significantly.